Internal electric field steering S-scheme charge transfer in ZnIn2S4/COF boosts H2O2 photosynthesis from water and air for sustainable disinfection - Linlin Zhuo; Shaofeng Dong; Yik Tung Sham; Jinpeng Zhang; Xiaoying Xu; Kenrick Chun Kiu Ho; Min Pan; Qiaoshan Chen; Guocheng Huang; Jinhong Bi (npj Clean Water)
Abstract The global need for clean water and sanitation drives the development of eco-friendly and efficient water treatment technologies to combat biological pollution from pathogens. In this study, a novel heterojunction photocatalyst was synthesized by incorporating ZnIn2S4 into covalent organic frameworks (COFs) to enable environmentally friendly hydrogen peroxide (H2O2) photosynthesis and explore its potential for in situ disinfection. The ZnIn2S4/COF photocatalyst achieved remarkable H2O2 yields of 1325 µmol∙g−¹∙h−¹, surpassing pristine COF and ZnIn2S4 by factors of 3.12 and 16.2, respectively. The produced H2O2 was efficiently activated into hydroxyl radicals (·OH) through reaction with Fe(II), enabling rapid sterilization via a photocatalysis-self-Fenton system. Mechanistic insights, supported by physicochemical characterizations and theoretical calculations, highlighted the role of the internal electric field (IEF) in enhancing carrier separation and transfer, thereby boosting photosynthesis efficiency. This work presents a sustainable approach to H2O2 photosynthesis and activation for disinfection, offering a promising solution to global water treatment challenges.